Analysis of pressure parameters in orthopedic footwear for people suffering from diabetic foot syndrome - Mikołajczyk, Zbigniew; Nowak, Iwona; Kuchyts, Yvan; Mikołajczyk-Solińska, Melania (Wydawnictwo Politechniki Łódzkiej, 2022)
The paper examines the anthropotechnical design of orthopedic footwear for patients with diabetic foot syndrome. A 3D distance knitted fabric is used for the shoe insert. For the purpose of the research, a 7 mm thick knitted fabric with transverse elasticity of 76 kPa was designed and produced on a doublebar warp knitting machine. With the use of the FreeMed Professional strain gauge mat, the pressures exerted by the foot on a „bare” walking surface and on the surface equipped with the distance knitted fabric were measured and compared, proving that in the latter case the unit pressure on the patient's foot decreased by 25%. The obtained measurements provide a good starting point for further research on the optimization of loads on the human foot, in case of various lower limbs diseases, including anatomical changes, as well as and in relation to people who are physically overloaded due to working in standing position or being in constant motion.
Keywords: diabetic foot; 3D distance knitted fabric; strain gauge mat; stopa cukrzycowa; dzianina dystansowa 3D; mata tensometryczna